Deploying and Improving Hadoop on PseudoDistributed Mode - Bhatia, Raj Kumari; Bansal, Aakriti (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Hadoop is an open source framework which comprises of Map Reduce and HDFS (Hadoop Distributed File System) which allows storage of data and computing capabilities on large scale. Hadoop is expanding every day and many cloud computing enterprises have been adapting it. Hadoop provides a platform to provide cloud computing services to customers. Hadoop can be run of any the three modes: Standalone, Pseudo-Distributed and Fully-Distributed. In this paper we have improved execution time by configuring different schedulers. We implemented our method over Hadoop 2.2.0 on Pseudo-Distributed mode which improves the overall job execution time.